The Effect of Open-Ended Cooperative Learning on Students' Civic Education Learning Outcomes - Taufika, Ryan; Ginting, Juriati (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2021)
Learning is basically the provision of knowledge given to students by students, using various models, strategies and methods in learning, not forgetting to also pay attention to students' psychological factors. A common problem faced in learning is that it is still difficult to express opinions during learning. This study uses a quantitative method which was carried out at SMK PAB 2 Helvetia which is located at Jalan Veteran, Manunggal Village, Kec. Labuhan Deli. Data were collected by means of observation and interviews, questionnaires, documentation and triangulation. The data were analyzed using analytical techniques using Product Moment. The sample of this study was taken based on the total sampling method, by taking the entire population as a sample. From the data obtained by researchers, it can be concluded that there is an effect of Open Ended (X) cooperative learning on student learning outcomes in Civics subjects with Human Rights (Y) material at the level of ? t?_hitung>t_tabel, namelyt_(hitung )=5,638 t_(tabel )= 1,and the correlation result r_xy = 0,700 is greater thant_tabel= 0,334 (0,700 > 0,334) then Ho is rejected and Ha is accepted, so the conclusion is